International remittances to Latin America and the Caribbean amid the Covid-19 crisis: A push for digitalization? - Verónica Frisancho Robles; Eric Parrado (Inter-American Development Bank (IDB), 2021)
Remittances constitute a significant safety net for millions of households in Latin America and the Caribbean (LAC). Consequently, changes in international transfers can be a crucial agent of transmission of the COVID-19 induced economic crisis from richer to poorer nations and from urban to rural areas. Relying on data on queries to the search engine Google between December 2018 and July 2021, this study looks at the evolution of demand for in-person versus digital international transfer services and evaluates if take-up rates of different types of service providers trace the initial drop and subsequent rebound of remittances. The recovery of remittances was accompanied by a modest and temporary increase in the interest in digital mechanisms for sending money to home countries, which is accompanied by lower demand for brick-and-mortar service providers.
Keywords: F24; G2; G5; 330; Remittances; COVID-19; Digital payments; Financial inclusion